LEARNERS' SPEAKING SKILLS WITH SPEECH DELAY BARRIERS IN PRIMARY SCHOOL - Fitri Siti Sundari; Arita Marini (PrimaryEdu : Journal of Primary Education, 2022)
This study aims to describe the speaking skills of learners who have speech delay barriers in elementary school. Qualitative research methods of case studies. Child research subjects who had speech delaybarriers. Data collection techniques in the form of oral tests, observations, interviews, and documentation. Instruments in the form of oral tests with the form of story texts and instruments in the form of interview question guides and observation guides. Data analysis includes data reduction, data presentation, and conclusions. The results showed that learners with  speech delay barriers had speech skills that were still less seen from the language and non-language aspects. This is due to individual factors of quiet speech delay learners and lack of confidence, family genetic factors that make learners experience speech delay,and environmental factors that makestudents' social interactions limited. Efforts applied in improving speech delay learners' speaking skills    are using concrete learning media in the form of images, applying drill methods and question and answer methods, and providing motivation.